Tidal pacing, skipped slips and the slowdown of Whillans Ice Stream, Antarctica. Issue 222 (2014) - Winberry, J. Paul; Anandakrishnan, Sridhar; Alley, Richard B.; Wiens, Douglas A.; Pratt, Martin J.
Abstract: We summarize new observations of the deceleration and stick–slip motion of Whillans Ice Stream (WIS), Antarctica. We refine the location of the large sticky spots that resist motion between slip events, the locations of which are controlled by the patterns of subglacial water flow. Our examination of the long-term velocity time series for the ice stream reveals that the decadal-scale deceleration is not occurring at a steady rate, but varies at the sub-decadal timescale. This unsteady deceleration modulates the temporal evolution of a broad ( 50 km across) surface-elevation bulge forming at the junction between the relatively narrow upstream portion of the ice stream and broad ice plain that constitutes the downstream end of WIS. Comparison of observations from April 2003 and November 2010 reveals significant changes in the tidally modulated stick–slip cycle that regulates motion on the ice plain. We observe that the timing of slip events has become less regular in response to decreased flow speed in the upstream portions of the ice stream. The decreased regularity of slip events has reduced the release of stored elastic strain during slip events, increasing the rate of deceleration.